2013
DOI: 10.1159/000353707
|View full text |Cite
|
Sign up to set email alerts
|

Association between Oral Health and the Risk of Lacunar Infarction in Japanese Adults

Abstract: Background: Poor oral health is associated with an increased risk of dementia in the elderly. One possible pathway linking these two phenomena is lacunar infarction, a potential cause of dementia. An association between poor oral health and an increased risk of ischaemic stroke has been recognised through the oral infection-inflammation pathway. However, little is known about whether poor oral health is associated with the progression of lacunar infarction. Objective: We examined the association between variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 34 publications
4
26
2
2
Order By: Relevance
“…A previous study demonstrated that PPD was increased in LI, but failed to demonstrate a relationship between clinical periodontal parameters and the presence of LI (Taguchi et al. ). Similarly, although our patients with LI showed worse periodontal conditions in terms of past (i.e., CAL) and current PD (i.e., FMBS and PPD), none of them were significantly associated with a higher risk of LI.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study demonstrated that PPD was increased in LI, but failed to demonstrate a relationship between clinical periodontal parameters and the presence of LI (Taguchi et al. ). Similarly, although our patients with LI showed worse periodontal conditions in terms of past (i.e., CAL) and current PD (i.e., FMBS and PPD), none of them were significantly associated with a higher risk of LI.…”
Section: Discussionmentioning
confidence: 95%
“…A 2014 meta-analysis reported that a periodontal disease increases the incidence of cerebrovascular disease [ 25 ]. In Japan, Taguchi et al reported a significant association among the number of lacunar infarctions, a type of cerebral infarction, and ABL [ 26 ]. However, a cohort study found no such significant association [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent report suggests an association between oral health and the risk of lacunar infarction [12]. Tooth-blushing and myofunctional therapy stimulate the secretion of saliva [13,14].…”
Section: Application To Oral Diseasesmentioning
confidence: 99%